Time advantage of HemoCue versus traditional complete blood count during cordocentesis. (18th June 2021) - Anastasio, Hannah B.; Mardis, Rachel; Khalifeh, Adeeb; Baxter, Jason; Berghella, Vincenzo; Al-Kouatly, Huda B.
Abstract: Objectives: During cordocentesis, a significant risk factor for adverse outcome is procedure length. One of the greatest contributors to total procedure length is the time that elapses between obtaining a fetal sample and receiving the results of the complete blood count (CBC) from the hospital laboratory. We aimed to evaluate whether there is an advantage to using a point of care hemoglobinometer (HemoCue) compared with traditional CBC during cordocentesis, measured in time elapsing between obtaining fetal sample, and available result. Secondarily we aimed to compare accuracy of HemoCue in relation to traditional CBC. Methods: A prospective cohort study was conducted on women undergoing cordocentesis and fetal transfusion for suspected fetal anemia from July 2016 to July 2018 at an urban academic medical center. Fetal blood samples were obtained during cordocentesis, and concurrently sent for traditional CBC, as well as immediately analyzed at bedside using a HemoCue machine. The time elapsing between the obtained fetal sample and availability of results with HemoCue versus traditional CBC were recorded. Primary outcome was time elapsed between obtaining fetal sample and result available for HemoCue versus traditional CBC. Secondary outcome was comparison of HemoCue and CBC hemoglobin values for accuracy. Results: Forty-five fetal samples were compared using CBC and HemoCue. Sixteen cordocentesis procedures were performed on 10 patients during the study period. Use of HemoCue was associated with a significantly shorter time to yield a fetal hemoglobin result, compared to traditional CBC (1.5 versus 5.5 min, p  = .0001). Results yielded by the HemoCue highly correlated to those yielded by traditional CBC ( R  = 0.96). Conclusions: Use of HemoCue during cordocentesis is associated with a 4-min time advantage over traditional CBC. Hemoglobin results yielded by HemoCue and traditional CBC are highly correlated. KEY MESSAGE: Use of a point-of-care hemoglobinometer is associated with a time advantage of 4 min over traditional complete blood count during cordocentesis. This represents a potentially modifiable risk factor for procedure length, and thus procedure complications.